Analisis Pengelolaan Zakat di Kabupaten Minahasa Tenggara: Penghimpunan, Pendistribusian, dan Pelaporan - Radlyah Hasan Jan; Faradila Hasan; Gisella Timbalo (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2023)
This study aims to analyze the collection, distribution, and reporting of zakat at the National Amil Zakat Agency in Southeast Minahasa Regency. This research is a qualitative approach (natural setting) using interviews and observation as data collection methods. The results of the study show that the management of zakat in Southeast Minahasa Regency is carried out by UPZ-UPZ in the Southeast Minahasa Regency, in this case the UPZ Al-Ansor Mosque and Ar-Rahman Mosque. The collection of zakat is preceded by outreach to the community via mosque loudspeakers and announcements when Friday prayers have been held. The collection of zakat fitrah is then carried out together with zakat mal in the month of Ramadan. The distribution of zakat is done by distributing the zakat to mustahik, at the time after the completion of the Eid al-Fitr prayer. As for zakat reporting, the National Amil Zakat Agency does not have a zakat report because the zakat reporting from the UPZ-UPZ is done through the Office of Religious Affairs in Belang District. This study highlights the current condition of zakat management which is not fully running optimally and suggests the need for increased government support to optimize the function of these zakat management institutions.